Penerapan Algoritma Regresi Linier Sederhana Dalam Memprediksi Keuntungan dan Kerugian Kelapa Sawit Pt. Sri Ulina Ersada Karina - Cici Erlangga Simbolon (Journal of Information System Research (JOSH), 2021)
Something that is processed in order to produce a maximum in predicting a data in the company so that it can be good. In data processing, PT.Sri Ulina Ersada Karina still uses manual calculations. For this reason, it is necessary to predict within the company so that there are no insurmountable losses and loss of customers who make big losses. It is for this reason that the authors make a study that discusses predicting the advantages and disadvantages of oil palm distribution at PT.Sri Ulina Ersada Karina. Testing data using the SPSS 17 application. This prediction is made in order to predict the coming year in order to overcome any losses. The existence of this prediction is also so that problems that often occur can be resolved